The enforcement of restorative justice in Indonesia criminal law - Virginia Garcia; Hari Sutra Disemadi; Barda Nawawi Arief (Faculty of Law, University of Muhammadiyah Malang, 2020)
Restorative Justice is a philosophy, process, ideas, theories and interventions that emphasize the improvement of the harm caused or expressed by criminal behavior. This process is in sharp contrast to the standard way of handling crime as is commonly carried out in criminal law in Indonesia. Restorative justice finds a foothold in the basic philosophy of the fourth principle of Pancasila, namely deliberation on priorities in decision making. The purpose of the settlement by mediating victims of violators is to humanize the justice system, justice that is able to answer what the real needs of victims, perpetrators and the community.